Cardiovascular and respiratory systems' signal simulation, processing and analysis for ICU, OR and telemedicine applications - Krishnan Shankar Muthu. (2008)
Including: 3 parts. Cardiovascular diseases are of grave concern to society and new techniques are needed for improving the diagnosis of those diseases. Application of intelligent signal processing techniques is essential for efficient diagnosis of cardiac diseases. Development of telemedicine systems is essential for communicating medical information from a home or a remote place to the hospital for prompt care. The report summarizes the development for new techniques for simulation, analysis, diagnosis and communication of cardiovascular signals.